ESP MATERIALS FOR MEDICAL RECORDS STUDENTS: AN EVALUATION STUDY - Yeni Nurmala Hidayati (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
An ESP course for medical students is intended to help them study their subject matters and in their future careers or jobs. The aim of this study was to evaluate whether the ESP materials for medical records and health information students in IIK satisfied their needs and their working environments. A careful examination of the perception of the students, the graduates and the users was considered to be predominant in evaluating the existing English materials. Structured questionnaires administered to the students, the graduates and the users were the instruments used to obtain the data in this study. The findings of the research showed that the existing materials during the college did not satisfy the students’ and the graduates’ needs. Some specific topics/issues, texts and vocabularies related to the medical contexts were highly required. As a conclusion, medical recorders are required to be taught with ESP materials as having relevancy with the students’ discipline in order to make the students motivate and encourage them in their academic knowledge and to ease the work-related activities in the future workplaces as well